2001
DOI: 10.1086/320284
|View full text |Cite
|
Sign up to set email alerts
|

An Infrared Camera for Leuschner Observatory and the Berkeley Undergraduate Astronomy Lab

Abstract: We describe the design, fabrication, and operation of an infrared camera which is in use at the 30-inch telescope of the Leuschner Observatory. The camera is based on a Rockwell PICNIC 256×256 pixel HgCdTe array, which is sensitive from 0.9-2.5 µm. The primary purpose of this telescope is for undergraduate instruction. The cost of the camera has been minimized by using commercial parts whereever practical. The camera optics are based on a modified Offner relay which forms a cold pupil where stray thermal radia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An off-the-shelf set of primary and secondary mirrors were not available from commercial vendors. However, Graham & Treffers (2001) 7 found that one could use a convex lens with a gold coating on one side as the secondary in order to function as a cost-effective convex mirror. We were able to utilize an Offner relay constructed in this way, that had been designed for a previous infrared instrument at the University of Michigan.…”
Section: Opticsmentioning
confidence: 99%
“…An off-the-shelf set of primary and secondary mirrors were not available from commercial vendors. However, Graham & Treffers (2001) 7 found that one could use a convex lens with a gold coating on one side as the secondary in order to function as a cost-effective convex mirror. We were able to utilize an Offner relay constructed in this way, that had been designed for a previous infrared instrument at the University of Michigan.…”
Section: Opticsmentioning
confidence: 99%
“…In the last few years, a number of cameras have utilized Offner re-imaging systems for these and other reasons. 4,5 In ASTROCAM, the only transmissive elements are the cryostat window and the filters.…”
Section: Design Criteriamentioning
confidence: 99%
“…Cassini has been sited about 65,000 km rather than 1200 km from Titan, giving it a small enough orbital velocity that its transmissions will not after all be Doppler shifted out of the bandwidth of the receiver. And it was a happy surprise to find that The Students' Obser-vatory of UC Berkeley, where old friends like Lawrence Aller and Daniel Popper plotted their first comet orbits and variable light curves, still exists and is used (Graham & Treffers 2001).…”
Section: Oh Isn't That Nice?mentioning
confidence: 99%